Religion and Memory the Importance of Monuments in Preserving Historical Identity - Kirsch, Jutta (Stuttgart Franz Steiner Verlag, 2021)
Inhaltsverzeichnis: Intro -- Acknowledgements -- Dedication -- Table of Contents -- List of Photographs -- Abstract -- Chapter One: Overview -- 1.1 Title -- 1.2 Introduction -- 1.3 Background -- 1.4 Problem Statement -- 1.5 Central Theoretical Argument -- 1.6 Aims and Objectives -- 1.7 Research Methods -- Chapter Two: The Tragedy of the 1915 Armenian Genocide -- 2.1 Introduction -- 2.2 Armenia Today -- 2.2.1 History and Fate of the Armenians -- 2.3 The Armenian Views of the Cause and Impact of the Genocide -- 2.3.1 The Regime of the Young Turks -- 2.4 Annihilation and Deportation of the Armenians -- 2.5 The German Role in the Armenian Conflict -- 2.5.1 The German Empire Supports Jihad -- 2.5.2 German's Confused Policy of Positioning Today -- 2.5.3 Summary of the Issue surrounding the Armenian Genocide -- 2.6 Primal Religion and Christianity in Armenia -- 2.6.1 The History of Christianity in Armenia -- 2.6.2 Mother Church Etchmiadzin -- 2.6.3 Bible Translation and Christian Culture in Armenia -- 2.7 Was the Armenian Genocide really a Genocide? -- 2.8 Conclusion -- Chapter Three: The Holocaust, Cause and Impact of National Socialism in Germany -- 3.1 Introduction -- 3.2 National Socialism as an Ideology and Pseudo-Religion -- 3.3 The History of the Holocaust -- 3.3.1 The Process of Coming to Terms with one's Past in the Soviet Zone of Divided Germany -- 3.3.2 The Process of Coming to Terms with the Past in Former West-Germany -- 3.4 The Blind Loyalty to Hitler's Religion, Transmission of Emotional Heritage -- 3.4.1 Transmission of Emotional Heritage through Perpetration -- 3.4.2 The Trauma of Holocaust Survivors -- Chapter Four: Theology, Reflection, Memory and Memorials -- 4.1 Introduction -- 4.2 Assmann's Communicative and Cultural Memory -- 4.2.1 Assmann's Analysis and how Cultural Memory works -- 4.3 Cultural Mnemonics as an Educational Memory in Judaism.
Literaturverzeichnis: Seite 249-272
Description based on publisher supplied metadata and other sources
Keywords: Electronic books